2014
DOI: 10.1186/preaccept-1701638048134699
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and manipulating the Mycobacterium tuberculosis transcriptome using a transcription factor overexpression-derived regulatory network

Abstract: Background: Mycobacterium tuberculosis senses and responds to the shifting and hostile landscape of the host. To characterize the underlying intertwined gene regulatory network governed by approximately 200 transcription factors of M. tuberculosis, we have assayed the global transcriptional consequences of overexpressing each transcription factor from an inducible promoter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
152
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(157 citation statements)
references
References 36 publications
3
152
0
2
Order By: Relevance
“…Transcript profiling of the M. tuberculosis cmr mutant compared with the same strain transformed with an integrated plasmid expressing cmr resulted in extensive complementation of the mutant transcription profile, indicating that the observed changes in transcription were mediated by disruption of the cmr gene (Table 1). Previous transcript profiling data obtained by 6-fold over-expression of cmr suggested that no genes were significantly regulated (≥2-fold, P ≤ 0.01) (25), hence, the cmr mutant to parent comparison undertaken here has revealed components of the Cmr regulon under laboratory conditions for the first time. Although the changes in transcript abundance reported by Rustad et al .…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Transcript profiling of the M. tuberculosis cmr mutant compared with the same strain transformed with an integrated plasmid expressing cmr resulted in extensive complementation of the mutant transcription profile, indicating that the observed changes in transcription were mediated by disruption of the cmr gene (Table 1). Previous transcript profiling data obtained by 6-fold over-expression of cmr suggested that no genes were significantly regulated (≥2-fold, P ≤ 0.01) (25), hence, the cmr mutant to parent comparison undertaken here has revealed components of the Cmr regulon under laboratory conditions for the first time. Although the changes in transcript abundance reported by Rustad et al .…”
Section: Resultsmentioning
confidence: 55%
“…Although the changes in transcript abundance reported by Rustad et al . did not meet the statistical criteria to be considered significant, nine Cmr-repressed genes ( rv0080, rv1738, rv2007c, rv2031c, rv2032, rv2623, rv2626c, rv3130c, rv3131 ) detected here were also repressed by Cmr when cmr was over-expressed (25). …”
Section: Resultsmentioning
confidence: 94%
“…Out of the TF perturbations simulated, MTB PROM 2.0 identified Rv0880 as a knockout that would exploit the drug-specific vulnerabilities, yielding a strong defect when knocked out in the presence of bedaquiline, but not in its absence (see Table S3 for full results). Rv0880 , under standard culture conditions, modulates the expression of 23 genes 17 , 17 of which were significantly differentially expressed when treated with bedaquiline (Figure 1B). The Rv0880 bedaquiline-response regulon also contains a notable number of upregulated genes (8 out of 17, Figure 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…9a). The promoter regions encompass all identified promoter and transcription factor binding elements identified525354. These regions were subcloned into TOPO vector by TA cloning (TOPO TA cloning kit, Life Technologies), propagated in TOP10 chemically competent E. coli , and sequenced to select for vectors that correctly amplified the PCR fragment.…”
Section: Methodsmentioning
confidence: 99%